2021
DOI: 10.3390/ijms22042016
|View full text |Cite
|
Sign up to set email alerts
|

Yes-Associated Protein 1 Is a Novel Calcium Sensing Receptor Target in Human Parathyroid Tumors

Abstract: The Hippo pathway is involved in human tumorigenesis and tissue repair. Here, we investigated the Hippo coactivator Yes-associated protein 1 (YAP1) and the kinase large tumor suppressor 1/2 (LATS1/2) in tumors of the parathyroid glands, which are almost invariably associated with primary hyperparathyroidism. Compared with normal parathyroid glands, parathyroid adenomas (PAds) and carcinomas show variably but reduced nuclear YAP1 expression. The kinase LATS1/2, which phosphorylates YAP1 thus promoting its degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The transcriptional co-activator YAP1 is involved in the modulation of core stem genes [19][20][21]. A recent report showed that YAP1 accumulation at the nuclear level is induced by calcium-sensing receptor (CASR) activation in PAds-derived cells [18]. In PAds-derived cells (n = 3), R568-mediated CASR activation increased SOX2 mRNA levels, while the stimulatory effect was abolished by YAP1 silencing (Figure 2F,G).…”
Section: Role Of Casr-stimulated Yap1 Signalingmentioning
confidence: 86%
See 4 more Smart Citations
“…The transcriptional co-activator YAP1 is involved in the modulation of core stem genes [19][20][21]. A recent report showed that YAP1 accumulation at the nuclear level is induced by calcium-sensing receptor (CASR) activation in PAds-derived cells [18]. In PAds-derived cells (n = 3), R568-mediated CASR activation increased SOX2 mRNA levels, while the stimulatory effect was abolished by YAP1 silencing (Figure 2F,G).…”
Section: Role Of Casr-stimulated Yap1 Signalingmentioning
confidence: 86%
“…In PAdsderived primary cell cultures, CASR activation by the selective agonist R568 increased the expression of SOX2, while POU5F1/OCT4 and NANOG were unaffected. Reduction of YAP1 nuclear accumulation by silencing YAP1 [18] abolished the stimulatory effect of CASR activation on SOX2 expression levels, thus suggesting that it is mediated by YAP1 signaling activation. Considering that both CASR and YAP1 feature as tumor suppressors in parathyroid adenomas, the induction of SOX2 expression may promote cell resting more than cell proliferation [36].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations